Optimization of Postharvest Handling of Eggplant Using the Taguchi Technique - Cortbaoui, Patrick E.; Ngadi, Michael O. (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
By quantifying and predicting postharvest quality losses in response to different environmental factors, the study offers valuable insights into enhancing postharvest management practices and minimizing quality loss of horticultural commodities like eggplant. Additionally, the manuscript highlights the potential of the Taguchi method as a robust design tool for postharvest quality in various crops, suggesting broader applicability beyond eggplant to other fruits and vegetables exposed to diverse environmental conditions. Taguchi technique was used to optimize the postharvest handling process to minimize quality loss of fresh eggplant (Solanum melongena L.). To date Taguchi approach has been widely used in various subject areas, but no application to postharvest quality has been reported until the present time with the exception of some previous work conducted by the same authors in 2015. Measuring postharvest losses is an essential operational strategy to enhance postharvest management and to curtail quality loss of fresh horticultural commodities. In this study, the Taguchi approach was able to quantify the quality for all combinations of environmental factors/levels (T, RH, Light & time) used in this experiment and were expressed in terms of Signal-to-Noise ratios. The highest ratio—which correlated with the least variability of the noise factors around the desired objective of this characteristic—was found for each quality attribute. The Taguchi technique has proven to be an effective tool for estimating and forecasting postharvest quality losses resulting from various combinations of environmental parameters. It has also been shown to identify the ideal conditions for handling and storing eggplant. As a result, this technique can enhance postharvest quality management from field to fork and alleviate quality loss of fresh fruits and vegetables. This technique could, therefore be recommended as a robust design of quality in postharvest technology and could be applied to many other crops exposed to various environmental conditions.